Targeting angiotensin type-2 receptors located on pressor neurons in the nucleus of the solitary tract to relieve hypertension in mice. Issue 3 (16th March 2021) - Mohammed, Mazher; Johnson, Dominique N; Wang, Lei A; Harden, Scott W; Sheng, Wanhui; Spector, Eliot A; Elsaafien, Khalid; Bader, Michael; Steckelings, U Muscha; Scott, Karen A; Frazier, Charles J; Sumners, Colin; et al.
Abstract: Aims: These studies evaluate whether angiotensin type-2 receptors (AT2Rs) that are expressed on γ-aminobutyric acid (GABA) neurons in the nucleus of the solitary tract (NTS) represent a novel endogenous blood pressure-lowering mechanism. Methods and results: Experiments combined advanced genetic and neuroanatomical techniques, pharmacology, electrophysiology, and optogenetics in mice to define the structure and cardiovascular-related function of NTS neurons that contain AT2R. Using mice with Cre-recombinase directed to the AT2R gene, we discovered that optogenetic stimulation of AT2R-expressing neurons in the NTS increases GABA release and blood pressure. To evaluate the role of the receptor, per se, in cardiovascular regulation, we chronically delivered C21, a selective AT2R agonist, into the brains of normotensive mice and found that central AT2R activation reduces GABA-related gene expression and blunts the pressor responses induced by optogenetic excitation of NTS AT2R neurons. Next, using in situ hybridization, we found that the levels of Agtr2 mRNAs in GABAergic NTS neurons rise during experimentally induced hypertension, and we hypothesized that this increased expression may be exploited to ameliorate the disease. Consistent with this, final experiments revealed that central administration of C21 attenuates hypertension, an effect that is abolished in mice lacking AT2R in GABAergic NTS neurons. Conclusion: These studies unveil novel hindbrain circuits that maintain arterial blood pressure, and reveal a specific population of AT2R that can be engaged to alleviate hypertension. The implication is that these discrete receptors may serve as an access point for activating an endogenous depressor circuit. Graphical Abstract: